Large‐sized rare tree species contribute disproportionately to functional diversity in resource acquisition in African tropical forest. Issue 8 (2nd April 2019) - Kearsley, Elizabeth; Hufkens, Koen; Verbeeck, Hans; Bauters, Marijn; Beeckman, Hans; Boeckx, Pascal; Huygens, Dries
Abstract: Increasing evidence is available for a positive effect of biodiversity on ecosystem productivity and standing biomass, also in highly diverse systems as tropical forests. Biodiversity conservation could therefore be a critical aspect of climate mitigation policies. There is, however, limited understanding of the role of individual species for this relationship, which could aid in focusing conservation efforts and forest management planning. This study characterizes the functional specialization and redundancy for 95% of all tree species (basal area weighted percentage) in a diverse tropical forest in the central Congo Basin and relates this to species' abundance, contribution to aboveground carbon, and maximum size. Functional characterization is based on a set of traits related to resource acquisition (wood density, specific leaf area, leaf carbon, nitrogen and phosphorus content, and leaf stable carbon isotope composition). We show that within both mixed and monodominant tropical forest ecosystems, the highest functional specialization and lowest functional redundancy are solely found in rare tree species and significantly more in rare species holding large‐sized individuals. Rare species cover the entire range of low and high functional redundancy, contributing both unique and redundant functions. Loss of species supporting functional redundancy could be buffered by other species in the community, including more abundant species. This is not the case for species supporting high functional specialization and low functional redundancy, which would need specific conservation attention. In terms of tropical forest management planning, we argue that specific conservation of large‐sized trees is imperative for long‐term maintenance of ecosystem functioning. Abstract : Large‐sized rare tree species in a tropical forest in the central Congo Basin disproportionately support high functional specialization and low functional redundancy in the tree community. Within the context of forest conservation for carbon mitigation initiatives, conservation of these rare species for long‐term maintenance of ecosystem functioning is crucial.